Ontological metaphors in the sexual expressions of young gay men from Lima about male sexual body parts - Atoccza Ramírez, Roger Yerson (2022)
The objective of this article was to determine the ontological metaphors in the sexual expressions of young gay men from Lima about male sexual body parts. To collect the data, 10 young gay men from Lima between the ages of 18 and 25 were interviewed. Thus, a total of 100 sexual expressions were recorded. Regarding the theoretical framework, the research had as theoretical bases the conceptual metaphor of the theorists Lakoff and Johnson (1998), and the classification of ontological metaphors of the linguist Buenafuentes (2015). The research reached the following conclusions: young gay men from Lima develop ontological metaphors that include comparisons with food, animals, objects and upper parts of the body around the head; there is a greater number of ontological metaphors referring to the penis; and the sexual expressions of young gay men from Lima are characterized by being loaded with jargon.